# Algebra 2

posted by Nan

The sequence is defined by a recursion formula. Write the first four terms of the sequence;

a_1=0; a_n=5a_n-1 +7

1. Steve

what's the problem? Just write them out:

a_1 = 0
a_2 = 5a_1 + 7 = 5*0+7 = 7
a_3 = 5a_2 + 7 = 5*7+7 = 42
and so on

## Similar Questions

1. ### math

-Write the arithmetic sequence 21,13,5,-3... in the standard form: a_n= -a_n=a_1+(n-1)d--so a_n=21+(n-1)-8 *a_n=-168-8n why isnt this right?
2. ### calculus

A) How do you prove that if 0(<or=)x(<or=)10, then 0(<or=)sqrt(x+1)(<or=)10?
3. ### Calculus

A) How do you prove that if 0(<or=)x(<or=)10, then 0(<or=)sqrt(x+1)(<or=)10?
4. ### calculus

A) How do you prove that if 0(<or=)x(<or=)10, then 0(<or=)sqrt(x+1)(<or=)10?
5. ### Math

Write the first four terms of the sequence defined by the recursion formula. a1 = 6 and an = 3an-1 for n ≥ 2
6. ### Algebra 2

The sequence is defined by a recursion formula. Write the first four terms of the sequence: a_1=9; a_n=3a_n-1
7. ### Algebra 2

The sequence is defined by a recursion formula.Write the first four terms; a_1=-5; a_n=2a_n-1 +7
8. ### Algebra 2

The sequence is defined by a recursion formula, write the first four terms of the sequence; a_1=100; a_n=1/2a_n-1 +4
9. ### math Help plz

1.Given a geometric sequence with a_1=6 and r=2/3, write an explicit formula for a_n, the nth term of the sequence. 2.A geometric sequence has a_4=4 and a_5=7. What is a?
10. ### Algebra II

1. Which represents the first two terms of the sequence: a_1 = 2 and a_n = -2(a_n-1)^2 option a. -8, -128 option b. 16, 1024 option c. -2, 16 option d. 2, -8 2. Which is the seventh term in the sequence: a_n = -1/125 * 5^n-1 option …

More Similar Questions